2007
DOI: 10.1007/s11554-007-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

A hardware architecture for real-time image compression using a searchless fractal image coding method

Abstract: In this paper we present a novel hardware architecture for real-time image compression implementing a fast, searchless iterated function system (SIFS) fractal coding method. In the proposed method and corresponding hardware architecture, domain blocks are fixed to a spatially neighboring area of range blocks in a manner similar to that given by Furao and Hasegawa. A quadtree structure, covering from 32 · 32 blocks down to 2 · 2 blocks, and even to single pixels, is used for partitioning. Coding of 2 · 2 blocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…From Table 4, it is found that the proposed architecture outperforms the architecture by Vidya [18], in terms of PSNR, encoding time and compression ratio for a larger image size, while both (the proposed and in [18]) architectures employ the same algorithm and the same partitioning scheme. Compared to the architecture by Jackson [8], the saving in execution time can be ascribed to the absence of domain search mechanism, as it employs no-search algorithm. This design requires 1047 clock cycles for encoding a 32 × 32 range block.…”
Section: Experimental Results and Comparison Of Performancesmentioning
confidence: 99%
See 3 more Smart Citations
“…From Table 4, it is found that the proposed architecture outperforms the architecture by Vidya [18], in terms of PSNR, encoding time and compression ratio for a larger image size, while both (the proposed and in [18]) architectures employ the same algorithm and the same partitioning scheme. Compared to the architecture by Jackson [8], the saving in execution time can be ascribed to the absence of domain search mechanism, as it employs no-search algorithm. This design requires 1047 clock cycles for encoding a 32 × 32 range block.…”
Section: Experimental Results and Comparison Of Performancesmentioning
confidence: 99%
“…The domain block position is fixed with respect to range block which again eliminates the requirement of storing the best matching domain index. Therefore, in [8] the compression ratio improvement is basically due to the no-search algorithm. The achieved CR is fixed (i.e., 5.12 and 22.26 for 4 × 4 and 8 × 8, respectively) in the proposed work for any preferred range block size, whereas for [8] it varies nearly from 3 to 28 due to the QT structure.…”
Section: Experimental Results and Comparison Of Performancesmentioning
confidence: 99%
See 2 more Smart Citations
“…In [17], the memory accesses of the application are simplified by ignoring interframe movements. On the other hand, ignoring inter-frame movement will lead to error blocks with greater magnitude, and therefore lower achievable compression ratios.…”
Section: The Qsdpcm Applicationmentioning
confidence: 99%